Venous thrombo‐embolism as a complication of cross‐sex hormone treatment of male‐to‐female transsexual subjects: a review. (15th August 2013) - Asscheman, H.; T'Sjoen, G.; Lemaire, A.; Mas, M.; Meriggiola, M. C.; Mueller, A.; Kuhn, A.; Dhejne, C.; Morel‐Journel, N.; Gooren, L. J.
Summary Administration of cross‐sex hormones to male‐to‐female transsexual subjects, usually oestrogens + often anti‐androgens, such as cyproterone acetate, carries a risk of venous thromboembolism (VTE). VTE usually occurs in the first year of oestrogen administration. Ethinyl oestradiol, due to its chemical structure, was in 2003 identified as a major factor in the occurrence of VTE. Most clinics do not prescribe ethinyl oestradiol any longer, but people who take hormones without medical supervision use often oral contraceptives containing ethinyl oestradiol, many times in overdose. Cessation of use of ethinyl oestradiol and peri‐operative thrombosis prophylaxis for surgery have reduced prevalence rate of VTE. Other oral oestrogens should not be overdosed, and transdermal oestrogen is to be preferred. Thrombosis prophylaxis for surgery is mandatory. It seems advisable to stop hormone use at least 2 weeks before major surgery, to be resumed only after 3 weeks following full mobilisation.